A new species of Miconia (Melastomataceae) endemic to western Jalisco, Mexico - Zabalgoitia, Alejandro; Figueroa, Dante S.; Muñiz-Castro, Miguel Á. (Phytotaxa, 2020)
Miconia vallartensis is a new species endemic to the western mountains of Jalisco, south of Puerto Vallarta, Mexico. Here we describe, illustrate and provide a key to Miconia vallartensis and morphologically similar species based on vegetative and reproductive characters. This species is easily differentiated from other species by its compact inflorescences, long trichomes and glabrescent pink to dark red flowering hypanthia with reflexed calyx teeth.